Dos nuevas especies de Iridopsis Warren (Lepidoptera, Geometridae) del norte de Chile Two new species of Iridopsis Warren (Lepidoptera, Geometridae) from northern Chile - Héctor A. Vargas (Revista Brasileira de Entomologia, 2007)
Se presentan descripciones de dos nuevas especies de Iridopsis Warren, 1894, del norte de Chile: I. hausmanni sp. nov., del valle de Azapa, Provincia de Arica; e I. parrai sp. nov., de la Pampa del Tamarugal, Provincia de Iquique. Los estados inmaduros de I. parrai se asocian con Prosopis tamarugo Phil. (Fabaceae). Esta es la primera mención de Iridopsis para Chile. Two new species of Iridopsis Warren, 1894, are described from northern Chile: I. hausmanni sp. nov. from the Azapa valley, Arica Province; and I. parrai sp. nov. from Pampa del Tamarugal, Iquique Province. The immature stages of I. parrai are associated with Prosopis tamarugo Phil. (Fabaceae). Photographs of the adults and figures of the male and female genitalia are included. This is the first mention of Iridopsis from Chile.